Preliminary findings on EEG controlled prosthetic hand for stroke patients based on motor control - Ab Aziz, Ab Wafi; Jalani, Jamaludin; Mohd Rejab, Sujana; Sadun, Amirul Syafiq (Springer, 2022)
This project established an electroencephalogram (EEG)-controlled prosthetic hand to help stroke patients with their rehabilitation exercises. The preliminary finding on the experiments to identify a suitable signal to control a servo motor using Minwave Mobile as the input signal is presented. Three methods are used to generate input signals; attention level (Experiment A), eye blink detection (Experiment B), and meditation level (Experiment C) using the EEG device based on four healthy human subjects. The generated input signal is then used to move the servo motor to a specific angle. All three methods are found to be capable of generating the input signals to move the servo motor to a specific angle with some limitations. Therefore, the use of one or two input actions was recommended to vary the angle movement in the prosthetic hand of stroke patients for future development.